1999
DOI: 10.1001/archinte.159.15.1705
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodules in Graves Disease and the Risk of Thyroid Carcinoma

Abstract: Background:The risk of thyroid carcinoma in patients with Graves disease has been particularly emphasized when nodules coexist with thyroid hyperplasia; a surgical approach has been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1
13

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 26 publications
(28 reference statements)
0
33
1
13
Order By: Relevance
“…In addition, thyroid nodule develops in approximately half of the patients with Graves' disease during the follow-up (4). There is an increased risk of thyroid cancer in presence of these nodules (3).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, thyroid nodule develops in approximately half of the patients with Graves' disease during the follow-up (4). There is an increased risk of thyroid cancer in presence of these nodules (3).…”
Section: Introductionmentioning
confidence: 99%
“…Small thyroid cancers are being discovered as incidental findings in Graves' disease patients (4,8,9), and in some studies Graves' disease patients with a small thyroid cancer have been found to have a better outcome than patients with a small thyroid cancer manifested clinically (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…La USG es hoy día la prueba de elección para el diagnósti-co de la EGBN (26)(27)(28). Permite valorar tanto el número, la magnitud y las características ecóicas de los nódulos como, utilizando el modo Doppler color, establecer el grado funcional de los mismos y compararlo con el del parénquima circundante.…”
Section: Discussionunclassified